A novel immunochemotherapy based on immunogenicity-activated and immunosuppression-reversed biomimetic nanoparticles. Issue 43 (3rd October 2022) - Zuo, Huaqin; Tao, Junxian; Wang, Manli; Xie, Xiaoyan; Sun, Mei
Abstract : PM–PLGA–DOX/GEM nanoparticles can enhance anti-tumor immunity by recruiting and activating cytotoxic T lymphocytes based on immunogenic activation and immunosuppressive reversion. Abstract : Studies show that infiltrated myeloid-derived suppressor cells (MDSCs) are vital in the immunosuppressive tumor microenvironment and account for lymphoma refractoriness and recurrence. Here, we developed a biomimetic nanoplatform (PM–PLGA–DOX/GEM) in which platelet membranes (PM) wrap PLGA nanoparticles co-loaded with doxorubicin (DOX) and gemcitabine (GEM). PM–PLGA–DOX/GEM would accumulate in tumor tissues because of the enhanced permeation and retention (EPR) effect and the tumor cell-induced platelet aggregation (TCIPA) effect. GEM could eliminate the MDSCs in tumor tissues, thereby reversing the immunosuppressive tumor microenvironment. Furthermore, DOX could invoke the immunogenic cell death (ICD) of lymphoma cells. Consequently, numerous T cells were recruited and activated to improve the therapeutic effects. This study will offer a potential platform for clinical treatment of lymphoma and other solid tumors.